The Effect of Cash Holding, Capital Structure, and Company Size on Profitability in the Pharmaceutical Sub-Industry Listed on the Indonesia Stock Exchange - Najiah, Saroya; Sutrisno, Bambang (Dinasti International Journal of Management Science, 2026)
The primary objective of this research is to examine the influence of cash holdings, capital structure, and company size on the profitability of pharmaceutical sub-industry firms listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. In this study, profitability is proxied by Return on Assets (ROA), while cash holdings are calculated using the ratio of cash to total assets. Furthermore, capital structure is represented by the Debt to Asset Ratio (DAR), and company size is determined by the natural logarithm of total assets. This research utilizes secondary data derived from annual financial reports retrieved from the official Indonesia Stock Exchange website. The data analysis employs panel data regression, which includes model selection stages via the Chow test, Hausman test, and Lagrange Multiplier test. The empirical results demonstrate that cash holdings, capital structure (DAR), and company size partially affect the profitability of companies within the pharmaceutical sub-industry. Simultaneously, these three independent variables are found to collectively impact profitability. These findings suggest that maintaining optimal cash management, a sound asset-based funding structure, and appropriate company scale play crucial roles in enhancing corporate profitability performance. Consequently, this study is expected to provide valuable insights for company management in shaping financial policies and assist investors in evaluating the financial performance of pharmaceutical companies in the Indonesian capital market.